Keys to success in high level water polo teams - Perez, M. del C. I.; Ordonez, E. G.; González, C. T. (International Journal of Performance Analysis in Sport, 2016)
The aim of this study was to identify specific offensive performance indicators that distinguish the top clubs from the others in the Male Honour Division of the Spanish Water Polo League. A total of 88 matches from the 2011-2014 seasons have been analysed. The offensive performance variables were divided into four groups, namely, playing situations, attacks outcome, origin of shots, and technical execution of shots. Univariate analyses (ANOVA, Kruskal-Wallis and generalised linear model (GLM) tests) were conducted to identify differences in the offensive variables between "strong", "medium" or "weak" teams' performances. A multinomial logistic regression was carried out to determine the variables that best distinguish the team level. The offensive variables that best classified the team level (61.9% of correct classification rate) were counterattack shots (p